Kebijakan Repatriasi Myanmar Terhadap Etnis Rohingya di Bangladesh Pada Tahun 2017-2019 - Tioho, Hikari Akimi; Putri, Penny Kurnia; Parameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This study aims to explain the reasons for the Myanmar government in issuing a repatriation policy to Rohingya in Bangladesh in 2017-2019, in terms of external determinants of foreign policy making through explanatory qualitative analysis. Ethnic conflict is one of Myanmar's biggest conflicts in the international world. The change of the attitude of the Myanmar government towards the Rohingya, who initially did not recognize them as part of Myanmar society, but then issued a repatriation policy in 2017-2019, sparked worldwide attention. The authors identify that the external determinants affecting Myanmar are the reactions of other countries and alliances. The reaction of other countries is in the form of pressure from regional countries such as Indonesia and Malaysia to become influential countries in ASEAN and to become Muslim-majority countries that fully support human rights as well as protection for the Rohingya ethnic group. Countries directly adjacent to Myanmar, such as Bangladesh, are the countries that host the most refugees have experienced negative impacts from the activities. In addition to reactions from other countries, alliance countries such as China are one of the factors that can influence policy making in which China, as a country that has influence over the economic, political and military conditions of Myanmar, as well as being Myanmar's strongest alliance state in international politics requires Myanmar to consider repatriation policy as a solution for the Rohingya problem. Keywords : Bangladesh, Myanmar, Repatriation, Rohingya